Peningkatan Hasil Belajar Ilmu Pengetahuan Sosial Siswa Menggunakan Model Kooperatif Tipe Student Team Achievement Division (STAD) di Sekolah Dasar - Firdaus, Firdaus; Hamimah, Hamimah; Desyandri, Desyandri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of the research was  to describe the student’s learning outcomes in IPS learning with STAD model in the fourth grade of  SDN 16 Campago Ipuh Bukittinggi. The kind of the research was Classroom action research that use quantitative and qualitative approaches in which the subject of this research are the teacher and 26 students of the fourth grade. The result of this research  was to show of the increasing of the plan, process, and learning outcomes. In conclusion, STAD model can increase the student’s learning outcomes in IPS learning.